The RTI story : power to the people - Roy, Aruna (New Delhi : Roli Books, 2018)
"The RTI Story: Power to the People is the story of a campaign that evolved into a genuine and vibrant people$1 (Bs movement. Culled from the voices of people, often such stories only feed into the research of scholars, largely unacknowledged and forgotten. The dominant narrative is always from the perspective of the ruler and single individuals. One had hoped that democracy would set it right. But the people who are the primary contributors to the discourse always remain on the fringes. Written by Aruna Roy with the MKSS collective, this book is for everyone who asks questions, seeks answers to fight corruption and injustice and challenges arbitrary power. It is a celebration of commitment laced with humour, the struggle, the songs, the theatres of protest, long spells on the street and drafting a peoples$1 (Blaw."--s
Keywords: Minimum wage; Mazdoor Kisan Shakti Sangathan (Organization); India--Rajasthan; Social justice